Effect of the Molecular Weight of Dispersant to the Slurry for Lead-Free Transparent Dielectric Films - Wang, Byung-Yong; Lim, Dae-Soon; Oh, Young-Jei (TAYLOR & FRANCIS LTD, 2009)
To manufacture a green sheet for the lead-free PDP transparent dielectric by tape casting method, the dispersion characteristics of the slurry prepared by different molecular weight of polymeric dispersant have been studied. The dispersion stability was enhanced as the molecular weight of a dispersant was lower. Rapid particle agglomeration occurred by bonding among of long polymer chains and it effected a exerted negative influence upon physical properties of the final dryed sheet. We have established optimum dispersion condition by measuring the speed, height and viscosity of the precipitates in suspension. Composition and rheological characteristics of the slurry were studied. When the amount of addition of the dispersant was small, polymer electrolytes on a particle surface were non-uniformly absorbed to an empty adhesion spot for other particles, with adhesion not reaching a saturated state, resulting in impossibility of uniform packing.
Keywords: SUSPENSIONS